PROBLEMATIKA STIGMA BURUK DAN INTOLERANSI ANAK "PUNK" - Nur Hana Putri Nabila (Jurnal Kommunity Online, 2022)
Religious moderation is one of the keys to creating tolerance and harmony. In a multicultural society like Indonesia, which has the largest Muslim population in the world, religious moderation is important. Religious moderation strives so that religious people are expected to treat others well, accept differences, and live together in peace and harmony. However, religious moderation in Islam is still lacking and there is a low sense of tolerance in society. One of them is that punk children are always underestimated when carrying out worship. Not only that. when they do good they are always suspected and underestimated. Therefore, the research method used is field research with a qualitative descriptive approach. The subjects in this study, namely the founder of Underground Tasawuf, namely Ustad Halim Ambiya, punk children, and street children who have settled in Underground Tasawuf. Data sourced from primary data and secondary data. The results of the study show that the implementation of religious moderation plays an important role in punk and street children after being educated through the Underground Sufism community.